2019
DOI: 10.1007/s10694-019-00914-9
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Determining the Onset of Backdraft Using Solid Fuels

Abstract: Backdraft is an explosive fire phenomenon which typically occurs during fire-fighting activities, occasionally leading to fire-fighter fatalities. Real backdraft incidents involve complex fuel gas mixtures consisting of the products of underventilated burning and pyrolysis following burnout. However, most experimental research into backdraft has used methane gas or flammable liquids as fuel. Some aspects of real backdraft behavior may have been overlooked as a consequence of this simplicity. A reduced scale se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…According to the experimental results, they established a theoretical model and deduced the critical condition of backdraft. Wu et al [ 26 , 27 ] conducted reduced-scale experiments to study temperature conditions and critical factors of backdraft. Their results indicated that before the opening of a compartment, maximum temperature and the CO/CO2 ratio in the compartment were crucial factors that determined whether backdraft occurred or not.…”
Section: Introductionmentioning
confidence: 99%
“…According to the experimental results, they established a theoretical model and deduced the critical condition of backdraft. Wu et al [ 26 , 27 ] conducted reduced-scale experiments to study temperature conditions and critical factors of backdraft. Their results indicated that before the opening of a compartment, maximum temperature and the CO/CO2 ratio in the compartment were crucial factors that determined whether backdraft occurred or not.…”
Section: Introductionmentioning
confidence: 99%
“…백드래프트에 대한 실험연구는 위험성 등을 고려해서 축소규모의 구획실을 대상으로 한 연구가 많다 (2)(3)(4)9) . 이러한 연구의 하나로서 Fleishmannn 등은 축소 구획실에서 메탄 가스연료에서 발생하는 백드래프트가 발생하는 연료농도 한계값과 압력양상을 검토한 바 있다 (3) .…”
unclassified